Surgical treatment of gynaecomastia in a Saanen goat - Toniollo, Gilson Hélio [UNESP] (2010)
Background: Gynaecomastia in male goats is characterized by abnormal development of the mammary gland. Enlarged udder may be observed cranially to the scrotum, which can occasionally reach the size of the testicles. The udder may carry functional glands and impair the animal's reproductive performance and welfare. The case of a successful surgical treatment of gynaecomastia in a high reproductive performance Saanen buck-goat is reported in the present study.Material, Methods & Results: The animal was admitted presenting significant augmentation of the mammary glands, which was clinically diagnosed as gynaecomastia. The male goat owned optimal phenotypic characteristics for the Saanen breed, which had been producing high performance descendents. The mammary glands had been impairing the goat's locomotion and sexual performance. Manual milking resulted in great amount of milk secretion. The animal presented anorexia and impaired sexual performance. After clinical and laboratorial evaluation, the animal was submitted to radical mastectomy. An elliptic skin incision was performed around each mammary gland. Subcuticular blunt dissection was accomplished to isolate the mammarian tissue from the abdominal muscular layer and the spermatic chord. The excised mass was sampled for histological assessment. Subcuticular layer and skin closure was carried in a routine fashion. Hygienization of the surgical wound was performed with 2,5% PVP-I solution for ten days. Additionally, an association of penicillin G benzathine and streptomycin, and fluxinin meglumine were also given. The surgical procedure was successfully accomplished without any peroperative complication. The excised mass was sampled for anatomic/histological assessment. Macroscopically, the left mammary gland presented 22 cm in length, 12 cm wide and 26 cm in diameter. The right gland presented 16 cm in length, 7 cm wide and 13,5 cm in diameter. The microscopic assessment revealed hyperplasia of the glandular ducts. No abnormalities resembling malignant mammary neoplasms or degeneration were observed. At the end of the treatment, the animal was completely recovered. The animal convalesced satisfactorily and surgical wound healed completely within the first 10 days post-op. The goat was not culled and returned to normal reproductive activity. Within 12 months of follow-up, the animal was able to produce high milk yield performance progenies.Discussion: This case report presented relevant aspects of the surgical management of gynaecomastia, especially to veterinary practitioners dealing with milk goats. Gynaecomastia is not as common as other reproductive disorders in domestic animals. In opposition to the findings of the present study, other trials revealed that gynaecomastia usually does not affect fertility, libido, ejaculate parameters and sexual performance of goats. However, it is important to consider that neoplasic disorders such as mammary adenocarcinoma may be present, even though these are rare complications. Last but not least, the decision making on mastectomy in the present study was crucial in order to reestablish the animal's welfare and its functionality in the farms reproduction program.